Developing anti-discrimination law in Europe.The 27 Member States compared - Chopin, Isabelle; Gounart, Eirini-Maria (Luxembourg, 2010)
"The Comparative Analysis provides a detailed comparison of the anti-discrimination legislation in the 27 EU Member States, as comprehensively described in the country reports written by the European Network of Legal Experts in the Non-discrimination Field and summarised in this publication. The grounds of discrimination listed in the Directives 2000/43/EC and 2000/78/EC are considered individually and collectively, while the overall purpose of this document is to provide an overview of the national legal framework across the EU."